The relationship between elements and manifestations of low self-control in a general theory of crime: Two comments and a test - Stylianou, Stelios (My University, 2002)
I discuss two issues about the empirical assessment of Gottfredson and Hirschi's (1990) general theory of crime. First, regarding the internal validity of corresponding causal models, I argue that more attention must be paid to the distinction between independent and dependent variables (elements versus manifestations of low self-control). Second, regarding the interpretation of statistical results, I argue that researchers should not lose sight of the distinction between statistical and substantive significance. I also report a test of the theory based on data from a representative sample of high school seniors in the United States. The results of the test show that low self-control is a correct and certain, yet weak, predictor of certain deviant behaviors (skipping class, traffic violations, cigarette smoking, and the use of alcohol and marijuana).
Keywords: Self-control; Offense; Self-control theory